A Neglected Source on the Life of Hasan-i Sabbah, the Founder of the Nizari "Assassin" Sect. Issue 1 (2nd January 2017) - Hillenbrand, Carole
ABSTRACT: This article translates into English for the first time a little-known Arabic account of the life of Hasan-i Sabbah, the famous leader of the Nizari Isma'ilis, known in Western Europe as the "Assassins". This account is found in a biographical dictionary, the Kitab al-Muqaffa' al-Kabir of al-Maqrizi. The content of the text is then analysed, and various aspects of Hasan's early career, his visit to Egypt and his military activities are discussed. Particular attention is paid in the commentary to certain unusual facets of his daʿwa included in this account; these are not found in the much better-known Persian narratives of Juvaini and Rashid al-Din.